2015
DOI: 10.1108/tr-01-2014-0003
|View full text |Cite
|
Sign up to set email alerts
|

Snow reliability and climate elasticity: case of a Slovak ski resort

Abstract: Purpose – The aim of this paper is to present the relationship between climate and tourism development data as an example of an emerging winter and ski tourism destination in Slovakia. Design/methodology/approach – The method aims to discover the relationship through snow-reliability and regression analyses and to further implicate the consequences of such established relationship under a changing (warming) climate. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 23 publications
1
32
0
Order By: Relevance
“…In Central Europe, Damm et al [26] found no significant relationship between the snow index and overnight stays in Czechia but a positive relationship with a magnitude of 3-6% in Slovakia, whereas Demiroglu et al [32] also revealed significant relationships between daily snow depth, visibility, and temperature and skier visits to a particular Slovak ski area, with the snow depth elasticity as high as 1.2, implying that the demand is positively and highly sensitive to changes in snow cover. Temperature, on the other hand, was a negative regressor, as lower temperatures implied a higher snow depth.…”
Section: Introductionmentioning
confidence: 97%
See 4 more Smart Citations
“…In Central Europe, Damm et al [26] found no significant relationship between the snow index and overnight stays in Czechia but a positive relationship with a magnitude of 3-6% in Slovakia, whereas Demiroglu et al [32] also revealed significant relationships between daily snow depth, visibility, and temperature and skier visits to a particular Slovak ski area, with the snow depth elasticity as high as 1.2, implying that the demand is positively and highly sensitive to changes in snow cover. Temperature, on the other hand, was a negative regressor, as lower temperatures implied a higher snow depth.…”
Section: Introductionmentioning
confidence: 97%
“…The relationship of weather and climate with ski area/resort/destination performance had been reported in a total of 22 papers at the time of the preparation of this manuscript. These studies provide us with statistical and econometric models for France [19], Switzerland [20], Austria [21][22][23][24], Italy [25], Germany, and Slovenia in the Alps [26], Sweden [27,28], Norway [29], and Finland [30,31] in Nordic Europe [26], Czechia, Slovakia [32], and Romania [33,34] in Eastern Europe [26], Spain in Western Europe [26], the USA [13,[35][36][37], Australia [6], and Japan [38].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations